The effect of a new sports drink on fatigue factors in competitive tennis athletes - Marks, B. L.; Angelopoulos, T.; Shields, E.; Katz, L. M.; Moore, T.; Hylton, S.; Larson, R.; Wingo, J. (Journal of Sports Sciences, 2006)
Competitive tennis can be considered to be an intermittent moderate to high intensity endurance sport where fatigue is compounded by heat and hydration issues. Thus, tennis athletes must maintain an adequate fuel-fluid balance throughout their competition. In college matches, it is common for players to compete in both doubles and single matches on the same day, often with only 45 minutes rest between matches. When difficult matches go three sets and thus last at least two hours, it is not unusual to see performance deteriorate rapidly by the 3rd set. Past research has shown that supplementing with a 6-8% carbohydrate (CHO) sports drink with electrolytes substantially reduces fatigue and assists to reduce dehydration. It has been suggested that adding a small amount of protein (PRO) to a sport drink would assist to delay fatigue by boosting insulin levels thereby sparing muscle glycogen stores. Therefore, the purpose of this study was to investigate whether ingestion of a new sport drink containing a small amount of protein at regular intervals would reduce fatigue in college tennis players.